Vladimir Platonovich Tsessevich (1907-1983): The Eminent Scientist, Organizer and Popularizator - Andronov, I. L (Одеські астрономічні публікації, 2017)
Reminiscences on Prof. Vladimir Platonovich Tsessevich (11.10.1907-28.10.1983), the fa- mous scientist, lecturer and organizer of science are presented.